Microenvironment Influences Odontogenic Mesenchymal Stem Cells Mediated Dental Pulp Regeneration - Huang, Xiaoyao; Li, Zihan; Liu, Anqi; Liu, Xuemei; Guo, Hao; Wu, Meiling; Yang, Xiaoxue; Han, Bing; Xuan, Kun (Frontiers in Physiology, 2021)
Dental pulp as source of nutrition for the whole tooth is vulnerable to trauma and bacteria invasion, which will cause irreversible pulpitis and pulp necrosis. Dental pulp regeneration is a valuable method to restore the viability of dental pulp and even the whole tooth. Odontogenic mesenchymal stem cells (MSCs) reside in dental pulp environment have been widely used in dental pulp regeneration, due to its immense potential to regenerate pulp-like tissue. Furthermore, the regenerative abilities of odontogenic MSCs are easily affected by the microenvironment they reside in, and the natural environment of dental pulp has proved capable of regulating odontogenic MSCs homeostasis, proliferation, and differentiation. Therefore, various approaches were applied to mimic the natural dental pulp environment in order to optimize the efficacy of pulp regeneration. And odontogenic MSC aggregates similar to the natural dental pulp environment have been proved to regenerate well-organized dental pulp both in preclinical and clinical trials. In this review, we summarize recent progresses in odontogenic MSCs-mediated pulp regeneration, and concentrate on the effect of microenvironment surrounding odontogenic MSCs in the achievement of dental pulp regeneration.